مقاصد بناء النفس الإنسانية في القرآن الكريم = The purposes of building the human soul in the Holy Quran - Mohamed Shousha, Hossam Moussa; Elatrash, Radwan Jamal Yousef; Al Hanai, Kahlan Ali (IIUM Press, International Islamic University Malaysia, 2020)
يهدف هذا البحث إلى الكشف عن النفس الإنسانية ومقاصد بنائها في القرآن الكريم، موضحاً مفهوم النفس الإنسانية في القرآن الكريم، ثم أحوالها المتنوعة -باختصار-كما ورد في القرآن، ثم يعمد البحث إلى تبيان مقاصد بناء النفس الإنسانية في القرآن الكريم ، والهدف الأسمى من البحث هو معرفة المقاصد القرآنية من بناء النفس الإنسانية، مع وضع برنامج عملي في شكل جدول زمني يمكن من خلاله بناء نفس مؤمنة سوية في شتى مناحي الحياة، ولما كان الأمر كذلك اعتمد البحث على المنهج الاستقرائي لجمع الآيات القرآنية الواردة في هذا الصدد، ثم المنهج الاستنباطي لاستخراج المنهج القرآني في بناء وتكوين النفس الإنسانية ومقاصد ذلك، مستعيناً في ذلك بالأحاديث النبوية الشريفة التي لها صلة بالموضوع. وقد توصل الباحث إلى عدد من النتائج، ومن أهمها: التعرف على مفهوم النفس الإنسانية في القرآن الكريم، وهو: القوى الكامنة في الجسم الإنساني، والتي هي مجمع عواطف الخير، ونوازع الشر، ومستقر الغرائز والنزعات والعواطف، والشهوات المحركة لهذا الجسم المادي في تصرفه واتجاهه. وأن أحوال النفس هي : الأمارة بالسوء واللوامة والمطمئنة. كما توصل إلى أن وسائل بناء ثم تربية وتقويم كل نفس تتنوع حسب كل حالة. وأن للقرآن الكريم مقاصد من بناء النفس الإنسانية وهي المقصد التعبدي والتربوي والمجتمعي والدعوي. أن العمل وفق ما أراد الله لتحقيق معنى الاستخلاف هو السعادة الحقيقية، كما أن للقرآن الكريم منهج متفرد في تحقيق هذه السعادة بمصاحبة السنة النبوية المطهرة التي لا تنفك عنه في البناء. ********************************************************************************* This research aims to reveal the human psyche and the purposes for building it in the Holy Qur’an, explaining the concept of the human psyche in the Holy Qur’an, then its various conditions -in short -as stated in the Qur’an, then the research explores the purposes of building the human psyche in the Holy Quran, and the supreme goal of the research It is the knowledge of the Qur’anic intentions from building the human soul, with setting a practical program in the form of a timetable through which the soul of a believer can be built together in various aspects of life, and as this was the case, the research relied on the inductive approach to collect the Qur’anic verses mentioned in this regard, then the deductive approach to derive And extract aphids C Quranic building and the formation of self-humanitarian purposes, the drawing on the Prophet's chatter that are relevant to the topic. The researcher reached a number of results, the most important of which are: Identifying the concept of the human psyche in the Holy Qur’an, which is: the powers inherent in the human body, which are the complex of good emotions, impulses of evil, and stable instincts, tendencies and emotions, and the driving desires of this material body in its behavior and direction . And that the conditions of the soul are: the evil, blaming and reassuring. He also concluded that the means of building, breeding and straightening each breath vary according to each case. And that the Holy Qur’an has intentions of building the human soul, which is the worship, educational, societal and liturgical destination. To work according to what God wanted to achieve the meaning of disagreement is true happiness, just as the Holy Qur’an has a unique approach in achieving this happiness with the accompaniment of the pure and prophetic Sunnah that is inevitable in building .